2015
DOI: 10.1002/acr.22492
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Comorbidity Burden Among Moderate‐to‐Severe Psoriasis Patients with Comorbid Psoriatic Arthritis

Abstract: ObjectiveTo compare the prevalence of comorbidities, health care utilization, and costs between moderate‐to‐severe psoriasis (PsO) patients with comorbid psoriatic arthritis (PsA) and matched controls.MethodsAdults ages 18–64 years with concomitant diagnoses of PsO and PsA (PsO+PsA) were identified in the OptumHealth Reporting and Insights claims database between January 2007 and March 2012. Moderate‐to‐severe PsO was defined based on the use of at least one systemic or phototherapy during the 12‐month study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 41 publications
3
46
1
4
Order By: Relevance
“…The total direct costs associated with psoriasis were estimated at 5 million dollars in the United States in 2006 (13); therefore, the cost of relapse and recurrence can be reduced from 7706 to 25 Euros by implementing nonpharmacological methods (8). Patient education is one of the best nonpharmacological methods and one of the most important roles of nurses (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total direct costs associated with psoriasis were estimated at 5 million dollars in the United States in 2006 (13); therefore, the cost of relapse and recurrence can be reduced from 7706 to 25 Euros by implementing nonpharmacological methods (8). Patient education is one of the best nonpharmacological methods and one of the most important roles of nurses (30).…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis accounts for 37% and 42% of skin irritations and pain complaints, respectively (12). Depression is also a common disorder in these patients (13). In a study by Ghorbani et al in 2012 on 854 patients with psoriasis, referred to Imam Khomeini Hospital from 2006 to 2011, it was revealed that 36% of the patients had more than 1 psoriasis-related disorder.…”
Section: Introductionmentioning
confidence: 99%
“…koszty terapii W przeprowadzonym niedawno badaniu na temat obciążenia ekonomicznego i chorób współistnie-jących u pacjentów z łuszczycą w porównaniu z grupą kontrolną stwierdzono, że u chorych na łuszczycę częściej występuje nadciśnienie tętnicze, cukrzyca typu 2, otyłość, zespół metaboliczny lub choroba niedokrwienna serca, co wiąże się często z koniecznością wczesnego włączenia kilku leków oraz zwięk-szeniem kosztów terapii i zmniejsza stopień przestrzegania zaleceń terapeutycznych. W porównaniu z grupą kontrolną pacjentom chorym na łuszczycę przepisywano na receptach większą liczbę różnych leków, częściej byli oni przyjmowani do szpitala, częściej korzystali z opieki doraźnej i ambulatoryjnej oraz ponosili znacząco większe koszty zakupu leków i inne koszty medyczne [35].…”
Section: Metody Leczenia łUszczycyunclassified
“…Такой широкий диапазон показателей рас-пространенности ПсА вероятнее всего объясняется расовыми различиями, генетическим фоном, кли-матогеографическими особенностями, а также ва-риабельностью клинической картины в дебюте за-болевания, отсутствием единых критериев диагно-стики и дифференциальной диагностики ПсА. В результате исследователи при составлении стати-стических сводок в группу ПсА относят разные кли-нико-анатомические проявления псориатической артропатии, такие как артралгия, воспалительные (артриты) и дистрофические процессы суставов (ар-трозы) [24].…”
unclassified
“…По мнению ря-да авторов, в 60-75% случаев суставной синдром наблюдается у больных с длительно существующим псориатическим процессом, реже суставные изме-нения предшествуют кожным (15%) или возникают одновременно с ними (10%) [10,53]. Есть данные о синхронном ухудшении клинического течения кож-ного и суставного синдромов [54].…”
unclassified